Internal fit of two all-ceramic systems and metal-ceramic crowns - Leandro Moura Martins; Fabio Cesar Lorenzoni; Alcides Oliveira de Melo; Luciana Mendonça da Silva; José Luiz G. de Oliveira; Pedro Cesar Garcia de Oliveira; Gerson Bonfante (University of São Paulo, 2012)
OBJECTIVES: The aim of this study was to investigate the internal fit (IF) of glass-infiltrated alumina (ICA - In-Ceram Alumina), yttria-stabilized tetragonal zirconia polycrystals (Y-TZP - IPS e.max ZirCAD), and metal-ceramic (MC - Ni-Cr alloy) crowns. MATERIAL AND METHODS: Sixty standardized resin-tooth replicas of a maxillary first molar were produced for crown placement and divided into 3 groups (n=20 each) according to the core material used (metal, ICA or Y-TZP). The IF of the crowns was measured using the replica technique, which employs a light body polyvinyl siloxane impression material to simulate the cement layer thickness. The data were analyzed according to the surfaces obtained for the occlusal space (OS), axial space (AS) and total mean (TM) using two-way ANOVA with Tukey 's multiple comparison test (p<0.05). RESULTS: No differences among the different areas were detected in the MC group. For the Y-TZP and ICA groups, AS was statistically lower than both OS and TM. No differences in AS were observed among the groups. However, OS and TM showed significantly higher values for ICA and Y-TZP groups than MC group. Comparisons of ICA and Y-TZP revealed that OS was significantly lower for Y-TZP group, whereas no differences were observed for TM. CONCLUSIONS: The total mean achieved by all groups was within the range of clinical acceptability. However, the metal-ceramic group demonstrated significantly lower values than the all-ceramic groups, especially in OS.